2010
DOI: 10.1017/s1751731110000169
|View full text |Cite
|
Sign up to set email alerts
|

A whole genome scan to detect quantitative trait loci for gestation length and sow maternal ability related traits in a White Duroc × Erhualian F2 resource population

Abstract: Gestation length and maternal ability are important to improve the sow reproduction efficiency and their offspring survival. To map quantitative trait loci (QTL) for gestation length and maternal ability related traits including piglet survival rate and average body weight of piglets at weaning, more than 200 F 2 sows from a White Duroc 3 Erhualian resource population were phenotyped. A genome-wide scan was performed with 194 microsatellite markers covering the whole pig genome. QTL analysis was carried out us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
(41 reference statements)
2
10
1
Order By: Relevance
“…Chen et al . (), using microsatellite markers, have also detected one QTL region on SSC2; however, that peak also does not overlap with ours.…”
Section: Significant Snps Associated With Gestation Length For the Twcontrasting
confidence: 75%
See 1 more Smart Citation
“…Chen et al . (), using microsatellite markers, have also detected one QTL region on SSC2; however, that peak also does not overlap with ours.…”
Section: Significant Snps Associated With Gestation Length For the Twcontrasting
confidence: 75%
“…; Chen et al . ). These QTL, however, are based on linkage maps with few genetic markers, resulting in large confidence intervals.…”
Section: Significant Snps Associated With Gestation Length For the Twmentioning
confidence: 97%
“…A QTL for ‘plasma FSH concentration’ (QTL #646, [ 26 ]) was found to overlap with CNVR43H and CNVR44H from high fertility group animals. Two low fertility group specific CNVRs (CNVR13L and CNVR39L) overlapped with two different QTLs for ‘gestation length’ (#21837, [ 27 ]; and #452, [ 28 ]). One QTL for ‘testicular weight’ (#6527, [ 29 ]) harboured CNVR5L, a low fertility group CNVR.…”
Section: Resultsmentioning
confidence: 99%
“…; Chen et al . ) utilized a limited number of DNA markers and employed F 2 populations with large linkage disequilibrium blocks, resulting in large genomic regions associated with GL. Limited genome‐wide association studies have provided more precise locations of potential QTL or have identified variants and candidate genes for GL in swine (Onteru et al .…”
Section: Single Marker Association Results Between Snps That Explainementioning
confidence: 99%